2001
DOI: 10.1002/ar.1035
|View full text |Cite
|
Sign up to set email alerts
|

It's ethical, but is it legal? Teaching ethics and law in the medical school curriculum

Abstract: While Western medical ethics has ancient roots in the teachings of Hippocrates, its standing in the undergraduate medical curriculum is a distinctly modern development. Today, all of the 127 accredited U.S. medical schools offer formal biomedical ethics instruction, and nearly all offer instruction in the related discipline of health law. This article describes how biomedical ethics and health law are taught at the University of Iowa College of Medicine, one of 12 medical schools that offers separate required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 17 publications
(10 reference statements)
0
25
0
2
Order By: Relevance
“…[5] Few studies have highlighted the importance of accrediting medical teachers with medical ethics course or having this subject integrated during graduation. [6] Medical educators have a great responsibility on them of both responsible and answerable to the society to produce quality medical professionals and also be a role model for the same cause to their students. Privatization and capitalism may be responsible for the degrading medical ethical values which are actually responsible for the breaches in basic principles of medical practice and resulting in ethical fallacies.…”
Section: Medical Teachermentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Few studies have highlighted the importance of accrediting medical teachers with medical ethics course or having this subject integrated during graduation. [6] Medical educators have a great responsibility on them of both responsible and answerable to the society to produce quality medical professionals and also be a role model for the same cause to their students. Privatization and capitalism may be responsible for the degrading medical ethical values which are actually responsible for the breaches in basic principles of medical practice and resulting in ethical fallacies.…”
Section: Medical Teachermentioning
confidence: 99%
“…It becomes an epitome of subject to prepare medical practitioners in their moral responsibilities and legal issues related to patient care. [6] A comprehensive evaluation of undergraduate curriculum in regards to ethical and legal medical practices is the need of the hour. Ethics of medical research on human subjects has been a matter of much analysis.…”
Section: Ethics In Medical Education and Researchmentioning
confidence: 99%
“…A growing number of medical programs has begun to use case-based discussions over lectures alone to teach law to professional students. 3-5 One example of such a program was the University of Connecticut’s Health Center which offered a law and ethics course developed by a professor at the University. This course for medical and dentistry students utilized small group sessions and case-based discussions to educate students.…”
Section: Case-based Discussionmentioning
confidence: 99%
“…3,11,12 The implementation of the mock Board of Pharmacy meeting is a positive innovation based on a pre- and post-test on student learning experience. A total of 143 students of the 153 enrolled in the class consented to participate in the 5 question assessment.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…At one United States medical school law was taught in lawyer-led groups;16 in another, the device of a mock trial,17 an educational method common in legal education, was used. Elsewhere, in Canada an evaluation of a mock trial found medical students felt it to be ‘contrived’18 thus damaging its educational impact.…”
Section: A Reviewmentioning
confidence: 99%